RELEVANCE OF THE SIMULATION CONCEPT Zh. BAUDRILLARD IN TODAY’S REALITIES - Зінченко, Н.; Штепа, О. (SWorldJournal, 2025)
The essence of the socio-political component of J. Baudrillard’s simulation concept is considered, the role of communication in general and mass media in particular in the process of "loss of the social" is analyzed, the significance of the simulation con